Reducing Computational Fluid Dynamics Simulation Cost by Intelligently Reducing Geometric Complexity - Porter, Stuart Ross (Curtin University, 2020)
Computational Fluid Dynamic (CFD) Simulations enable a wide range of analysis but are costly to perform. This research looks at taking existing geometry from Building Information Models or CAD, and performing Geometric Abstraction to make them ready for simulation quickly, as well as reducing the computational cost to simulate them. The aim is to make CFD more accessible, so it can be applied more readily to existing and new problems.